Evaluation of the dimensions of the tsunami evacuation path for the community of Air Tawar Barat Village, North Padang District, Padang City, Based on Geographic Information System (GIS) - Ashar, Faisal; Yusup, Iqbal Maulana; Rifwan, Fitra; Adreas, Laras Oktavia (Universitas Negeri Padang, 2021)
Air Tawar Barat Village is included in the High-Risk Zone (area with a high level of vulnerability to tsunamis) in Padang City, so very severe damage likely occurs in the event of a tsunami. The characteristics of the tsunami in Padang City are local tsunamis or short-range tsunamis, where the time interval for tsunami arrivals is between 20-30 minutes. Based on these conditions, a tsunami evacuation route is urgently needed by the community. The current evacuation route is still ineffective because the distance that must be covered is 3-5 km in less than 30 minutes. This study aims to evaluate the evacuation routes that are less effective by comparing the evacuation routes from the government with the results of GIS analysis. The method used in this research is Network Analyst. The results of this study found that the time needed to evacuate was 10 minutes by going to 26 P-TES. Where 24 P-TES are located on the UNP campus, 1 is in the Air Tawar Timur Village and 1 is a planned P-TES. The evacuation route generated from the results of the GIS analysis is more effective than the route from the government because the route to P-TES is closer than having to leave the tsunami zone so that it is more likely to be taken by the community.